Pemberdayaan Kader Kesehatan dalam Upaya Pencegahan Stunting pada Anak di Puskesmas Perumnas II Kota Pontianak: Dissemination of Stunting Prevention in Children at the Public Health Center II in Pontianak City - Sri Wahdaningsih; Siti Nani Nurbaeti; Shoma Rizkifani; M Rafly Agustriangga; Risa Indriyani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Stunting is a chronic malnutrition problem characterized by short stature in children. The high prevalence of stunting in the long term in children will impact economic losses for Indonesia. Nowadays, nutritional problems are not only seen as health problems but have become a shared responsibility, and they need attention from all sectors, including educational institutions such as the Faculty of Medicine. The leading cause of stunting is malnutrition for a long time. Community Service Activities (PKM) aim to equip the Perumnas II Health Center cadres with information, education, and skills related to information on stunting prevention. This PKM activity consists of several activities, including designing educational methods, stunting educational media, and administering pretests and posttests. The results show an increase in the understanding of cadres with the indicator that the average pretest score is 55 and the average posttest score is 71.75. In conclusion, there has been an increase in the understanding of the Perumnas II Health Center cadres.